2008
DOI: 10.1111/j.1465-7295.2007.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

After‐school Program Effects on Behavior: Results From the 21st Century Community Learning Centers Program National Evaluation

Abstract: "This paper presents evidence on after-school programs' effects on behavior from the national evaluation of the U.S. Department of Education's 21st Century Community Learning Centers after-school program. Findings come from both of the study's components: (1) an elementary school component based on random assignment of 2,308 students in 12 school districts and (2) a middle school component based on a matched comparison design including 4,264 students in 32 districts. Key findings include higher levels of negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…Similarly, the meta-analysis by Zief et al (2006) showed that 84% of the outcomes measured in behavioral after-school programs showed no effects. Also, the resultant negative effects observed in the current study, are consistent with the findings presented in recent, large-scale studies of afterschool programs (James-Burdumy et al, 2008;Linden et al, 2011). However, the evaluation of a prosocial behavior program ⅐ 21 findings in this study deviate from the findings by Durlak et al (2010) in relation to the effectiveness of SAFE social and emotional learning after-school programs as the Mate-Tricks program followed SAFE practices in that it was sequenced (builds on concepts over the sessions), involved active learning (e.g., role-plays), included a focus on skill development (such as conflict resolution and emotional skills), and the children, facilitators, and parents were explicitly made aware of the program outcomes.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Similarly, the meta-analysis by Zief et al (2006) showed that 84% of the outcomes measured in behavioral after-school programs showed no effects. Also, the resultant negative effects observed in the current study, are consistent with the findings presented in recent, large-scale studies of afterschool programs (James-Burdumy et al, 2008;Linden et al, 2011). However, the evaluation of a prosocial behavior program ⅐ 21 findings in this study deviate from the findings by Durlak et al (2010) in relation to the effectiveness of SAFE social and emotional learning after-school programs as the Mate-Tricks program followed SAFE practices in that it was sequenced (builds on concepts over the sessions), involved active learning (e.g., role-plays), included a focus on skill development (such as conflict resolution and emotional skills), and the children, facilitators, and parents were explicitly made aware of the program outcomes.…”
Section: Discussionsupporting
confidence: 82%
“…In summary, it appears that after-school programs are a challenging context in which to improve personal and social outcomes. This is evidenced by prior studies with null or negative effects (James-Burdumy et al, 2008;Zief et al, 2006), reduced effects of non-SAFE programs (Durlak et al, 2010), and an identified disparity between the effectiveness of SEL programs delivered in and out of school (Durlak et al, 2011).…”
Section: Research On the Effectiveness Of Social And Emotional Learnimentioning
confidence: 83%
See 2 more Smart Citations
“…It is likely that because continued funding was not tied to PA and FV, these objectives were not a high priority. 26,27 Third, after-school programs may need to develop PA specialists who are responsible for delivering activity to all the after-school age groups. In the first intervention year, one site developed stations where one GL's entire job was to implement organized PA.…”
Section: Implications For Research and Practicementioning
confidence: 99%